2002
DOI: 10.1152/ajpregu.00364.2001
|View full text |Cite
|
Sign up to set email alerts
|

Aging and assessment of physiological strain during exercise-heat stress

Abstract: . Aging and assessment of physiological strain during exercise-heat stress. Am J Physiol Regulatory Integrative Comp Physiol 282: R1063-R1069, 2002 10.1152/ajpregu.00364.2001.-The purpose of this study was to evaluate the physiological strain index (PSI) for different age groups during exercise-heat stress (EHS). PSI was applied to three different databases. First, from young and middle-age men (21 Ϯ 2 and 46 Ϯ 5 yr, respectively) matched (n ϭ 9 each, P Ͼ 0.05) for maximal aerobic power. Subjects were heat ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
(46 reference statements)
2
14
0
Order By: Relevance
“…Noteworthy, reports suggest that even short-term exercise training programs which elicit improvements in cardiorespiratory function may have a beneficial effect on thermoregulatory function during a heat stress. Moran et al (2002) showed that older (69 years) men who underwent a 16-week aerobic exercise training demonstrated a significantly reduced level of physiological strain during exercise-induced heat stress compared with younger (26 years) individuals. When combined, these studies demonstrate that physical fitness (as indicated by _ V O 2max ) rather than age is a more important indicator of work-heat tolerance.…”
Section: Aging and Heat Balance During Exercisementioning
confidence: 99%
See 2 more Smart Citations
“…Noteworthy, reports suggest that even short-term exercise training programs which elicit improvements in cardiorespiratory function may have a beneficial effect on thermoregulatory function during a heat stress. Moran et al (2002) showed that older (69 years) men who underwent a 16-week aerobic exercise training demonstrated a significantly reduced level of physiological strain during exercise-induced heat stress compared with younger (26 years) individuals. When combined, these studies demonstrate that physical fitness (as indicated by _ V O 2max ) rather than age is a more important indicator of work-heat tolerance.…”
Section: Aging and Heat Balance During Exercisementioning
confidence: 99%
“…An increasing number of studies show that aerobic fitness and selected morphological factors can profoundly influence an individual's capacity to thermoregulate during work in the heat and may be more important determinants than aging per se in influencing work-heat tolerance (Cheung et al 2000;Moran et al 2002;Pandolf 1991Pandolf , 1997. Typically, older people have lower maximal aerobic power, higher adiposity and smaller stature and body mass compared with younger adults (Kenny et al 2008).…”
Section: Aging and Heat Balance During Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…PSI is therefore applied in this study to measure how rest breaks influence the recovery of the heat strain process. PSI has been shown to effectively differentiate the heat strain associated with different climatic conditions, hydration levels, types of clothing including protective clothing, different exercise intensities, gender and the effects of aging [36][37][38]. It is an algorithm combining data from the heart rate and core temperature, in which output is scaled from 0 to 10 where 0 represents "no strain" and 10 "very high physiological strain".…”
Section: Measurementsmentioning
confidence: 99%
“…BMI is a useful factor for determining obesity (9). The PSI was developed to evaluate heat and physiological strain by measuring heart rate (HR) and core body temperature (10). The HSSI, established and evaluated by Dehghan et al is an index that evaluates emotional and perceptual variables using questionnaire.…”
Section: Introductionmentioning
confidence: 99%